The Role of Cyclo(His-Pro) in Neurodegeneration - Grottelli, Silvia (Int J Mol Sci, 2016)
Neurodegenerative diseases may have distinct genetic etiologies and pathological manifestations, yet share common cellular mechanisms underpinning neuronal damage and dysfunction. These cellular mechanisms include excitotoxicity, calcium dysregulation, oxidative damage, ER stress and neuroinflammation. Recent data have identified a dual role in these events for glial cells, such as microglia and astrocytes, which are able both to induce and to protect against damage induced by diverse stresses. Cyclo(His-Pro), a cyclic dipeptide derived from the hydrolytic removal of the amino-terminal pyroglutamic acid residue of the hypothalamic thyrotropin-releasing hormone, may be important in regulating the nature of the glial cell contribution. Cyclo(His-Pro) is ubiquitous in the central nervous system and is a key substrate of organic cation transporters, which are strongly linked to neuroprotection. The cyclic dipeptide can also cross the brain-blood-barrier and, once in the brain, can affect diverse inflammatory and stress responses by modifying the Nrf2-NF-κB signaling axis. For these reasons, cyclo(His-Pro) has striking potential for therapeutic application by both parenteral and oral administration routes and may represent an important new tool in counteracting neuroinflammation-based degenerative pathologies. In this review, we discuss the chemistry and biology of cyclo(His-Pro), how it may interact with the biological mechanisms driving neurodegenerative disease, such as amyotrophic lateral sclerosis, and thereby act to preserve or restore neuronal function.